Juventudes transfronteiriças: (re)existência cultural e transnacional de um coletivo angolano em São Paulo - Paiva, Maria Claudia Sant'Anna de (2018)
Today we live in times of globalization, a scenario marked by the great circulation of material goods, capital, information and, above all, people. Technology provides greater flow, exchange, sharing of content, images and imagery. Scenarios are reshaped and people across the globe can connect in various ways, both with other subjects and other territories. The boundaries become porous, conform scenarios marked by dispute and conflict and are redesigned by their subjects in displacement. Within this large movement of sharing, and more specifically in São Paulo, you will find the young people from the Angolan Muxima collective in the Diaspora. Together with it’s narratives and trajectories, this dissertation aims to understand the ways in which youth and immigrant practices are capable of creating a living, pulsating and symbolic scenario within the contemporary metropolitan experience, in which the insertion of culture, politics and communication in the daily life of these subjects is capable of contributing to changes in the "inevitable" perspective of permanence, within contexts of urban segregation and exclusion. In the same way, as in their struggles against racism, they promote and reformulate counter-narrative structures and configurations that are emerging in a "local" and "global" way. The methodological course was anchored in the combination of theoretical references with qualitative techniques (ethnographic observation, in-depth interviews and virtual ethnography), in order to empirically dive into this universe and to answer in what way these immigrants create new ways to (re)exist and resist, as well as (re)construct their lives in transboundary, linking, revisiting and resignifying memories existing their bodies